Effect of Gold Price, Nickel Price, Used Exchange, Dow Jones Industrial Average, and FTSE Malaysia KLCI on Sharia Share Price Index (Sharia Ida) on The Indonesia Stock Exchange in the Period of January 2020 - December 2020 - marselia purnama purnama; Vivin Hanitha; Hendra Hendra (eCo-Buss, 2021)
In 2021, Indonesia is known as the country with the largest Muslim population in the world, which is 231,069,932 (data from the Ministry of Trade 2018) or 231 million Muslim population, which is equivalent to 12.7 percent of the Muslim population worldwide. With the largest Muslim population, the Indonesian stock exchange must provide investment facilities that are in accordance with Islamic teachings. So that the Indonesian Sharia Stock Index was formed in 2011. The index consists of all sharia shares listed on the Indonesia Stock Exchange. Many factors affect the price movement of Islamic stock indexes, including gold prices, nickel prices, USD exchange rates, Dow Jones Industrial Average and FTSE Malaysia KLCI. This study focuses on the object of research in the form of the influence of gold prices, nickel prices, USD exchange rates, Dow Jones Industrial Average, and FTSE Malaysia KLCI on the Sharia Stock Price Index in the research period from January 2020 to December 2020, and obtained a total of 230 data. This study uses the Ordinary Least Square method with the classical assumption test, multiple linear regression analysis, simultaneous test (f test), partial test (t test), and coefficient of determination test. The results of the test concluded that gold prices, nickel prices, Dow Jones Industrial Average, and FTSE Malaysia KLCI had a significant effect on Islamic IDX partially during the study period, while partially the USD exchange rate had no significant effect on Sharia IDX. Simultaneously, gold prices, nickel prices, USD exchange rates, Dow Jones Industrial Average, and FTSE Malaysia KLCI have a significant influence on Sharia IDX during 2020 with an adjusted R2 of 0.905720 or 90.57%, while the remaining 9.43% is influenced by other variables. which were not investigated in this study. Keywords: Gold Price, Nickel Price, USD Exchange, Dow Jones Industrial Average, and FTSE Malaysia KLCI, IDX Syariah